INTENSIFICATION VECTORS OF TRADE INTEGRATION OF THE POST-SOVIET COUNTRIES - Tetiana Tsygankova; Olena Iatsenko (Izdevnieciba "Baltija Publishing", 2020)
The study analyzes the dynamics of the development of integration processes. It is determined that the current stage of development is characterized by a change in the structure of the World Trade in favor of services and innovative products; by dynamic growth of trade in intermediate goods and services within global value chains. Trade integration covers a much broader network of participants, including bilateral, multilateral and interregional initiatives. The regional trade agreements (WTO-extra, WTO-plus) are being deepened and expanded. It is determined that the most common form of integration processes is the establishment of the Free Trade Zones, in particular on the basis of bilateral initiatives. Based on this, the bilateral trade relations between the post-Soviet countries and their trading partners (Poland, Italy, Switzerland, Bulgaria, Turkey, Czech Republic, Great Britain, Finland, Sweden, Netherlands, Germany, Romania, China) were analyzed. The index of trade complementarity was calculated and analyzed in order to identify the compliance of the export structure of the post-Soviet countries with the general structure of imports of these trading partners for high-tech product groups, in particular: machines and apparatuses for soldering and welding (code 8515 according to UKTZED (Ukrainian Commodity Coding System)), transmission shafts and bearing housings (code 8483), machines and mechanisms for harvesting and threshing crops (code 8433), spare parts and aggregates for metalworking equipment (code 8466), pumps for liquids (code 8413), burners for solid fuel or gas (code 8416), equipment for filtering and cleaning liquids and gases (code 8421), woodworking machines (code 8465), spare parts for motor vehicles (code 8708), electrical transformers (code 8504)). The geographical vectors of strengthening bilateral trade in the studied countries are substantiated based on the assessment of the calculated trade complementarity index. It was proposed to use the world experience based on certain key promising areas of international trade development in the context of the COVID-19 pandemic.